Pengaruh Pendapatan, Resiko, Premi, dan Informasi terhadap Preferensi Masyarakat Golongan Menengah ke Atas pada Produk Asuransi - Rullisha, Nova (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This research aims to determine the income, risk, premium and information that is prefered by the people within the middle upper class on insurance product. The type of research is an explanatory reseach with logistic regression method. The result showed that each variables significantly influence the peopleâ€™s preference. Â Keyword: peopleâ€™s preference, insurance